2004
DOI: 10.1177/1359104504041923
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Views of the Impact of Childhood Brain Tumours and Treatment on Young People’s Social and Family Functioning

Abstract: This article describes the long-term impact of childhood brain tumours on eight families, using an interpretative phenomenological analysis (IPA) approach. Two major themes emerged from the data: the impact of the illness and treatment on the child's current functioning, and how parents live day-today with the threat of future relapse or further long-term physical and psychological complications. A number of subcategories emerged from these themes, including the difficulties obtaining special educational needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(102 citation statements)
references
References 26 publications
0
101
0
Order By: Relevance
“…Vance and colleagues [35] uncovered two consistent themes after conducting semistructured interviews: (1) peer exclusion and being bullied; and (2) the discrepancy between their child's social relationships prior to cancer treatment and the subsequent downfall with peers following the return to school. As well, in Upton and Eiser's study, [34] almost half the mothers of children with brain tumors reported their child was socially isolated and half of these mothers felt their child's behavior limited social opportunities.…”
Section: Evidence For Deficits In Social Competencementioning
confidence: 96%
“…Vance and colleagues [35] uncovered two consistent themes after conducting semistructured interviews: (1) peer exclusion and being bullied; and (2) the discrepancy between their child's social relationships prior to cancer treatment and the subsequent downfall with peers following the return to school. As well, in Upton and Eiser's study, [34] almost half the mothers of children with brain tumors reported their child was socially isolated and half of these mothers felt their child's behavior limited social opportunities.…”
Section: Evidence For Deficits In Social Competencementioning
confidence: 96%
“…Both anecdotally and qualitatively, parents have expressed how their child seems ''different'' following treatment (Vance, Eiser, & Horne, 2004). Assisting parents in processing these changes and developing an understanding or expectation of these changes may be helpful, particularly because family processes may moderate the extent to which neurocognitive impact may influence psychosocial outcomes (Patel & Carlson-Green, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The demands or burdens experienced by caregivers are associated with reports of their health; caregivers who experience more demands report less optimal health (Klassen et al, 2007; Klassen et al, 2011; Raina et al, 2004; Vance, Eiser, & Horne, 2004). As Raina proposed, caregivers who perceive that their survivor has less than optimal health undergo more caregiver demands (Bandura, 1991; Hovén et al, 2011), a relationship which is also tested in this research.…”
mentioning
confidence: 99%